A fine mist method for constructing low-temperature locking and high-temperature guiding wet Janus antibacterial temperature-sensitive cotton fabric and a preparation method thereof

CN122879972APending Publication Date: 2026-10-09ZHEJIANG SCI TECH UNIV SHAOXING KEQIAO RES INST CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611233945.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0002]棉织物由天然纤维素构成,纤维表面富含羟基,亲肤透气,是贴身、户外、康复纺织品主流基材,但天然棉存在两大短板:其一,棉吸水储水量大,潮湿环境极易滋生致病菌,传统银离子、季铵盐抗菌整理仅依靠物理吸附附着纤维,水洗数次后抗菌性能大幅衰减,重金属抗菌剂存在皮肤刺激、生物蓄积风险;其二,纯棉无温度自适应功能,低温散热快、高温闷汗黏身,穿戴舒适度差

Benefits of technology

[0019](1)实现棉织物双侧功能差异化构筑。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879972A_ABST
    Figure CN122879972A_ABST
Patent Text Reader

Abstract

A preparation method of low-temperature temperature-locked and high-temperature moisture-conducting Janus antibacterial temperature-sensitive cotton fabric by fine mist method: the cotton fabric is activated by epoxy, one side is deposited with tannic acid by fine mist to form a hydrophilic antibacterial layer through ring-opening covalent grafting; the other side is deposited with aminoethyl methacrylate to introduce polymerizable double bonds, and then PEGDM and BA temperature-sensitive liquid are deposited by fine mist, and the free radical polymerization anchors the PEG-BA hydrophobic temperature-sensitive layer. The obtained fabric has a Janus structure with different properties on both sides, one side is hydrophilic and antibacterial, and the other side is hydrophobic and temperature-sensitive. The covalent bonding of tannic acid endows the fabric with durable antibacterial property, the antibacterial rate is ≥99.9%, and after 50 times of washing, it is still ≥95%; the PEG-BA layer shrinks at low temperature to lock moisture, and expands at high temperature to promote moisture permeability, the difference of water vapor permeability at 0~40℃ is ≥2.0. The process is green and high in fastness, and is suitable for outdoor cold protection, sports warming and rehabilitation nursing textiles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of intelligent functional textile materials technology, specifically relating to a method for preparing a low-temperature heat-locking, high-temperature moisture-wicking Janus antibacterial temperature-sensitive cotton fabric using a fine mist method. Background Technology

[0002] Cotton fabrics are made of natural cellulose, and the fiber surface is rich in hydroxyl groups, making them skin-friendly and breathable. They are the mainstream base material for close-fitting, outdoor, and rehabilitation textiles. However, natural cotton has two major drawbacks: First, cotton absorbs and retains a large amount of water, and pathogenic bacteria can easily grow in humid environments. Traditional silver ion and quaternary ammonium salt antibacterial finishing relies solely on physical adsorption to adhere to the fibers, and the antibacterial performance is greatly reduced after several washes. Heavy metal antibacterial agents pose risks of skin irritation and bioaccumulation. Second, pure cotton lacks temperature self-adaptation. It dissipates heat quickly at low temperatures but becomes stuffy and sticky at high temperatures, resulting in poor wearing comfort.

[0003] Existing Janus moisture-wicking cotton fabrics generally suffer from problems such as complex preparation processes, insufficient bonding strength of functional layers, large amounts of finishing agents, and thick coatings that clog fiber pores, making it impossible to integrate intelligent temperature response functions.

[0004] The relevant published patent CN117384129B only achieves single-sided antibacterial properties of tannic acid, without intelligent temperature control; CN118223456A has a full-area PNIPAM coating, but its temperature-sensitive response behavior is opposite to that of the human body. In summary, the industry lacks an integrated preparation process that is compatible with cotton fibers, can achieve low-temperature heat retention, high-temperature moisture conduction and positive temperature control, Janus double-sided partitioning, covalent long-lasting antibacterial properties, and low-damage organic solvent fine mist copolymerization. Summary of the Invention

[0005] The technical problem to be solved by this invention is to provide a method for constructing a low-temperature heat-locking, high-temperature moisture-wicking Janus antibacterial thermosensitive cotton fabric using a fine mist method and the preparation method thereof. Using cotton fabric as the substrate, the cotton fibers are first etherified and epoxidized using an epichlorohydrin-sodium hydroxide aqueous system to introduce epoxy active sites. Then, a tannic acid aqueous solution is sprayed onto one side of the fabric using a fine mist method, where phenolic hydroxyl groups are covalently grafted with epoxy ring-opening technology to construct a long-lasting hydrophilic antibacterial layer. On the other side of the fabric, an aminoethyl methacrylate (DMAEMA) aqueous solution is sprayed using a fine mist method, where epoxy and amino groups add polymerizable methacrylic acid double bonds to the fiber surface. Next, a thermosensitive solution of polyethylene glycol dimethacrylate (PEGDM), butyl acrylate (BA), and azobisisobutyronitrile (AIBN) is prepared using anhydrous DMF and sprayed onto the double bond surface using a fine mist method. Low-temperature, short-time free radical copolymerization is then performed to covalently anchor the PEG-BA temperature-responsive hydrophobic layer. After washing to remove residual additives, a Janus cotton fabric with one hydrophilic antibacterial side and one thermosensitive hydrophobic side is obtained.

[0006] To address the aforementioned technical problems, this invention provides a method for preparing a low-temperature heat-locking, high-temperature moisture-wicking Janus antibacterial thermosensitive cotton fabric using a fine mist method, comprising the following steps:

[0007] (1) Pretreatment of cotton fabric and epoxy activation treatment: The cotton fabric is ultrasonically cleaned with anhydrous ethanol and deionized water in sequence to remove surface dust and oil. Then, the cleaned and decontaminated cotton fabric is immersed in an aqueous activation solution containing epichlorohydrin and sodium hydroxide. The hydroxyl groups on the surface of cellulose undergo etherification reaction to introduce epoxy active groups, thus obtaining epoxy cotton fabric.

[0008] (2) Single-sided construction of hydrophilic antibacterial layer: Tannic acid TA functional liquid is deposited on one side of the surface of epoxidized cotton fabric by fine mist method, and heat treatment is performed to open the ring covalent grafting of tannic acid phenolic hydroxyl groups and fiber epoxy groups to form a stable hydrophilic antibacterial functional layer.

[0009] (3) Introduction of polymerizable carbon-carbon double bonds on one side: The aqueous solution of aminoethyl methacrylate (DMAEMA) is deposited on the other side of the epoxidized cotton fabric using a fine mist method. The epoxy group undergoes ring-opening addition with the amino group, and polymerizable methacrylate double bonds are grafted onto the fiber surface.

[0010] (4) Constructing a temperature-responsive hydrophobic layer: First, polyethylene glycol dimethacrylate (PEGDM) prepolymer is synthesized; dibutyltin dilaurate (DBTDL) catalyst is added to the synthesis system, and the amount of DBTDL added is 0.15 wt% of the total mass of the reactants. Then, PEGDM, butyl acrylate (BA), and free radical initiator AIBN are mixed to prepare a temperature-sensitive finishing solution, which is deposited on one side of the cotton fabric with active methacrylic acid groups by fine mist method. Free radical polymerization occurs with the polymerizable double bonds on the surface of the cotton fabric to construct a PEG-BA temperature-responsive hydrophobic functional layer.

[0011] (5) Washing and drying post-treatment: wash away unreacted small molecules and residual additives to obtain a low-temperature heat-locking and high-temperature moisture-wicking Janus antibacterial temperature-sensitive cotton fabric with hydrophilic antibacterial properties on one side and temperature-responsive hydrophobic properties on the other side.

[0012] Preferably, in step (1), the mass fraction of epichlorohydrin is 8-15 wt%, sodium hydroxide is 2-5 wt%, the epoxidation heat treatment temperature is 80-110℃, and the heat treatment time is 5-12 min.

[0013] Preferably, in step (2), the tannic acid functional liquid has a tannic acid mass fraction of 1~1.5 wt%, a curing temperature of 160~190℃, and a processing time of 3~8 min.

[0014] Preferably, the DMAEMA mass fraction in step (3) is 5~8 wt%.

[0015] Preferably, in step (4), the mass ratio of PEGDM to BA in the temperature-sensitive finishing solution is 3:1 to 10:1; the amount of free radical initiator AIBN added is 0.2 to 0.5 wt%; the free radical polymerization temperature is 70 to 90℃, and the time is 12 to 36 h.

[0016] Preferably, the cleaning process in step (5) is to first soak in DMF to remove organic residues, then wash with deionized water multiple times, and dry at a temperature of 60~90℃.

[0017] To solve the second technical problem mentioned above, the present invention also provides a low-temperature heat-locking, high-temperature moisture-wicking Janus antibacterial temperature-sensitive cotton fabric prepared by the above preparation method. The fabric has a double-sided anisotropic Janus wetting structure, with one side of the fabric being a tannic acid covalently grafted hydrophilic antibacterial layer and the other side of the fabric being a PEG-BA covalently polymerized temperature-responsive hydrophobic layer.

[0018] Advantages of this invention:

[0019] (1) Realize the functional differentiation of cotton fabrics on both sides.

[0020] Janus structure design is achieved by forming a hydrophilic antibacterial layer and a temperature-responsive hydrophobic layer on both sides of the fabric using a fine mist method. The fine mist method involves directional unilateral deposition, and tannic acid, DMAEMA, and PEG-BA are covalently grafted onto the epoxidation activation sites to form a stable asymmetric wetting interface.

[0021] (2) It has intelligent temperature response and moisture permeability.

[0022] PEG-BA temperature-sensitive segments undergo a hydrophilic-hydrophobic conformational change with temperature: at low temperatures (0℃), the segments curl up, the yarn pores shrink, resulting in low water vapor permeability and heat retention; at high temperatures (40℃), the segments expand, the pores expand, water vapor is rapidly expelled, and moisture permeability is increased, dynamically adapting to the human body's hot and cold environment. The PEG-BA temperature-sensitive layer can change the movement of its segments with changes in ambient temperature, adjusting the surface wetting state and water vapor diffusion channels, achieving dynamic adjustment of the fabric's moisture permeability. The hydrophobic side has a water contact angle ≥125° at room temperature, and the water vapor permeability is dynamically adjustable within the 0~40℃ range. The fabric possesses reversible temperature-responsive moisture permeability; low water vapor permeability in low-temperature environments and expansion of the temperature-sensitive polymer segments in high-temperature environments increase the water vapor transport rate, achieving intelligent regulation of human body temperature and humidity.

[0023] (3) Excellent antibacterial properties.

[0024] The plant-derived antibacterial components of tannins are covalently bonded, achieving an antibacterial rate of ≥99.9% against Escherichia coli and Staphylococcus aureus; the antibacterial rate remains ≥95% after 50 standard water washes. It contains no heavy metals or toxic antibacterial agents and is suitable for medical and intimate apparel.

[0025] (4) It has high bonding strength and good durability.

[0026] Functional components are fixed to the surface of cotton fibers through chemical bonding, avoiding the problem of easy peeling off of traditional physical coatings.

[0027] (5) The preparation process is green and efficient.

[0028] The precise deposition of fine mist microdroplets reduces the amount of finishing agent used compared to traditional padding, eliminates the need for large-area immersion, and significantly reduces wastewater discharge. It can be integrated into continuous atomization finishing production lines, resulting in high production efficiency. Without a thick, full-area coating, only a thin layer of polymer is grafted onto the fiber surface, preserving fabric breathability and avoiding the stuffiness and stiffness issues common with temperature-sensitive coated fabrics, resulting in a soft hand feel. The fine mist method features low dosage, high utilization rate, and ease of continuous processing, making it suitable for industrial-scale promotion.

[0029] The fabric is used in outdoor cold-proof fabrics, sports thermal underwear, close-fitting thermal regulating textiles, and rehabilitation and nursing cotton fabrics. Detailed Implementation

[0030] Example 1

[0031] First, the cotton fabric was ultrasonically cleaned with anhydrous ethanol and deionized water for 30 min to remove oil and impurities from the fabric surface. Then, the clean cotton fabric was immersed in an aqueous activating solution containing epichlorohydrin (10 wt%) and sodium hydroxide (3 wt%). The epoxidation heat treatment temperature was 90℃ for 8 min, resulting in the etherification of hydroxyl groups on the cellulose surface and the introduction of epoxy active groups, thus obtaining epoxidized cotton fabric. Next, a 1.2 wt% tannic acid aqueous solution was prepared and deposited onto one side of the epoxidized cotton fabric using a fine mist method. The curing temperature was 170℃ for 4 min. Then, a 7 wt% aminoethyl methacrylate (DMAEMA) aqueous solution was prepared and deposited onto the other side of the epoxidized cotton fabric using a fine mist method, and treated at 60℃ for 40 min. The epoxy groups on the fiber surface underwent a ring-opening addition reaction with the amino groups in the DMAEMA molecules, grafting polymerizable methacrylate carbon-carbon double bond active sites onto the other side of the epoxidized cotton fabric. This process was used to further prepare PEG-BA temperature-responsive functional materials. First, polyethylene glycol (PEG, molecular weight approximately 4000) was vacuum dried at 70°C for 10 h, then dissolved in 60 mL of dichloromethane, and 10 g of molecular sieve was added for dehydration. Ethyl methacrylate-2-isocyanate (2-IEM) and DBTDL were added to the above system, with a PEG to 2-IEM mass ratio of 18:1 and DBTDL added at 0.15 wt%. The mixture was stirred at 30°C for 4 days to allow the PEG terminal hydroxyl groups to fully react with the isocyanate groups, obtaining a PEG-based dimethacrylate prepolymer. After the reaction, the resulting product was added to a large amount of n-hexane for precipitation. The precipitate was collected by filtration and vacuum dried at 40°C for 8 h to obtain PEGDM oligomers. Subsequently, the PEGDM oligomer was melted at 70°C and mixed uniformly with butyl acrylate (BA, 12 wt%) and azobisisobutyronitrile (AIBN, 0.3 wt%). This mixture was then dissolved in 10 mL of DMF to prepare a mixed solution, which was deposited onto the other side of the cotton fabric with the introduced methacrylic acid active groups using a fine mist method. The fabric was then heated at 80°C for 14 h to undergo free radical polymerization, allowing it to form a stable bond with the substrate through double bond polymerization, thus forming a PEG-BA temperature-responsive surface. Finally, the prepared bifunctional cotton fabric was washed with dichloromethane, DMF, and distilled water to remove unreacted small molecules, and dried at 80°C for 2 h to obtain a smart cotton fabric with a dual-functional structure of a hydrophilic antibacterial layer and a temperature-responsive hydrophobic layer.

[0032] Performance Testing: After tannic acid treatment, the hydrophilicity of the fabric surface was significantly enhanced, exhibiting excellent hydrophilic properties. The water contact angle on the other side of the surface after PEG-BA functionalization reached over 130°, exhibiting obvious hydrophobic characteristics, proving that the fabric forms a distinct Janus wetting structure. Antibacterial performance results showed that the tannic acid-functionalized surface exhibited excellent antibacterial effects against Escherichia coli and Staphylococcus aureus, with an inhibition rate exceeding 99.9%. After 50 standard washes, the fabric still maintained an antibacterial rate of over 95%, indicating that the functional layer has good durability and stability. Water vapor transmission performance testing results showed that the water vapor transmission rate of the cotton fabric at a low temperature of 0℃ was 4.17 g / m³. 2 / d, when the temperature rises to 40℃, the moisture permeability increases, reaching 6.32. .

[0033] Example 2

[0034] First, the cotton fabric was ultrasonically cleaned with anhydrous ethanol and deionized water for 30 min to remove oil and impurities from the fabric surface. Then, the clean cotton fabric was immersed in an aqueous activating solution containing epichlorohydrin (12 wt%) and sodium hydroxide (3 wt%). The epoxidation heat treatment temperature was 85℃ for 10 min, resulting in the etherification of hydroxyl groups on the cellulose surface and the introduction of epoxy active groups, thus obtaining epoxidized cotton fabric. Next, a 1.5 wt% tannic acid aqueous solution was prepared and deposited onto one side of the epoxidized cotton fabric using a fine mist method. The curing temperature was 170℃ for 5 min. Then, an 8 wt% aminoethyl methacrylate (DMAEMA) aqueous solution was prepared and deposited onto the other side of the epoxidized cotton fabric using a fine mist method, and treated at 60℃ for 40 min. The epoxy groups on the fiber surface underwent a ring-opening addition reaction with the amino groups in the DMAEMA molecules, grafting polymerizable methacrylate carbon-carbon double bond active sites onto the other side of the epoxidized cotton fabric. This process was used to further prepare PEG-BA temperature-responsive functional materials. First, polyethylene glycol (PEG, molecular weight approximately 4000) was vacuum dried at 70°C for 10 h, then dissolved in 60 mL of dichloromethane, and 10 g of molecular sieve was added for dehydration. Ethyl methacrylate-2-isocyanate (2-IEM) and DBTDL were added to the above system, with a PEG to 2-IEM mass ratio of 18:1 and DBTDL added at 0.15 wt%. The mixture was stirred at 30°C for 4 days to allow the PEG terminal hydroxyl groups to fully react with the isocyanate groups, obtaining a PEG-based dimethacrylate prepolymer. After the reaction, the resulting product was added to a large amount of n-hexane for precipitation. The precipitate was collected by filtration and vacuum dried at 40°C for 8 h to obtain PEGDM oligomers. Subsequently, the PEGDM oligomer was melted at 70°C and mixed uniformly with butyl acrylate (BA, 10 wt%) and azobisisobutyronitrile (AIBN, 0.3 wt%). This mixture was then dissolved in 10 mL of DMF to prepare a mixed solution, which was deposited onto the other side of the cotton fabric with the introduced methacrylic acid active groups using a fine mist method. The fabric was then heated at 80°C for 14 h to undergo free radical polymerization, allowing it to form a stable bond with the substrate through double bond polymerization, thus forming a PEG-BA temperature-responsive surface. Finally, the prepared bifunctional cotton fabric was washed with dichloromethane, DMF, and distilled water to remove unreacted small molecules, and dried at 80°C for 2 h to obtain a smart cotton fabric with a dual-functional structure of a hydrophilic antibacterial layer and a temperature-responsive hydrophobic layer.

[0035] Performance Testing: After tannic acid treatment, the hydrophilicity of the fabric surface was significantly enhanced, exhibiting excellent hydrophilic properties. The water contact angle on the other side of the surface after PEG-BA functionalization reached over 132°, exhibiting obvious hydrophobic characteristics, proving that the fabric forms a distinct Janus wetting structure. Antibacterial performance results showed that the tannic acid-functionalized surface exhibited excellent antibacterial effects against both Escherichia coli and Staphylococcus aureus, with an inhibition rate exceeding 99.9%. After 50 standard washes, the fabric still maintained an antibacterial rate of over 95%, indicating that the functional layer has good durability and stability. Water vapor transmission performance testing results showed that the water vapor transmission rate of the cotton fabric at a low temperature of 0℃ was 3.85 g / m³. 2 / d, when the temperature rises to 40℃, the moisture permeability increases, reaching 6.74. .

[0036] Example 3

[0037] First, the cotton fabric was ultrasonically cleaned with anhydrous ethanol and deionized water for 30 min to remove oil and impurities from the fabric surface. Then, the clean cotton fabric was immersed in an aqueous activating solution containing epichlorohydrin (10 wt%) and sodium hydroxide (4 wt%). The epoxidation heat treatment temperature was 100℃ for 6 min, resulting in the etherification of hydroxyl groups on the cellulose surface and the introduction of epoxy active groups, thus obtaining epoxidized cotton fabric. Next, a 1 wt% tannic acid aqueous solution was prepared and deposited onto one side of the epoxidized cotton fabric using a fine mist method. The curing temperature was 180℃ for 4 min. Then, a 7 wt% aminoethyl methacrylate (DMAEMA) aqueous solution was prepared and deposited onto the other side of the epoxidized cotton fabric using a fine mist method, and treated at 60℃ for 40 min. The epoxy groups on the fiber surface underwent a ring-opening addition reaction with the amino groups in the DMAEMA molecules, grafting polymerizable methacrylate carbon-carbon double bond active sites onto the other side of the epoxidized cotton fabric. This process was used to further prepare PEG-BA temperature-responsive functional materials. First, polyethylene glycol (PEG, molecular weight approximately 4000) was vacuum dried at 70°C for 10 h, then dissolved in 60 mL of dichloromethane, and 10 g of molecular sieve was added for dehydration. Ethyl methacrylate-2-isocyanate (2-IEM) and DBTDL were added to the above system, with a PEG to 2-IEM mass ratio of 18:1 and DBTDL added at 0.15 wt%. The mixture was stirred at 30°C for 4 days to allow the PEG terminal hydroxyl groups to fully react with the isocyanate groups, obtaining a PEG-based dimethacrylate prepolymer. After the reaction, the resulting product was added to a large amount of n-hexane for precipitation. The precipitate was collected by filtration and vacuum dried at 40°C for 8 h to obtain PEGDM oligomers. Subsequently, the PEGDM oligomer was melted at 70°C and mixed uniformly with butyl acrylate (BA, 20 wt%) and azobisisobutyronitrile (AIBN, 0.4 wt%). This mixture was then dissolved in 10 mL of DMF to prepare a mixed solution, which was deposited onto the other side of the cotton fabric with the introduced methacrylic acid active groups using a fine mist method. The fabric was then heated at 85°C for 16 h to undergo free radical polymerization, allowing it to form a stable bond with the substrate through double bond polymerization, thus forming a PEG-BA temperature-responsive surface. Finally, the prepared bifunctional cotton fabric was washed with dichloromethane, DMF, and distilled water to remove unreacted small molecules, and dried at 80°C for 2 h to obtain a smart cotton fabric with a dual-functional structure of a hydrophilic antibacterial layer and a temperature-responsive hydrophobic layer.

[0038] Performance Testing: After tannic acid treatment, the fabric surface exhibited significantly enhanced hydrophilicity, demonstrating excellent hydrophilic properties. The other surface, after PEG-BA functionalization, showed a water contact angle exceeding 133°, exhibiting obvious hydrophobic characteristics, proving the formation of a distinct Janus wetting structure. Antibacterial performance results showed that the tannic acid-functionalized surface exhibited excellent antibacterial effects against both *Escherichia coli* and *Staphylococcus aureus*, with an inhibition rate exceeding 99.9%. After 50 standard washes, the fabric maintained an antibacterial rate of over 95%, indicating good durability and stability of the functional layer. Water vapor transmission performance testing results showed that the cotton fabric had a water vapor transmission rate of 3.71 g / m³ at 0°C. 2 / d, when the temperature rises to 40℃, the moisture permeability increases, reaching 6.89. .

[0039] Example 4

[0040] First, the cotton fabric was ultrasonically cleaned with anhydrous ethanol and deionized water for 30 min to remove oil and impurities from the fabric surface. Then, the clean cotton fabric was immersed in an aqueous activating solution containing epichlorohydrin (10 wt%) and sodium hydroxide (4 wt%). The epoxidation heat treatment temperature was 100℃ for 6 min, resulting in the etherification of hydroxyl groups on the cellulose surface and the introduction of epoxy active groups, thus obtaining epoxidized cotton fabric. Next, a 1.2 wt% tannic acid aqueous solution was prepared and deposited onto one side of the epoxidized cotton fabric using a fine mist method. The curing temperature was 180℃ for 5 min. Then, a 7 wt% aminoethyl methacrylate (DMAEMA) aqueous solution was prepared and deposited onto the other side of the epoxidized cotton fabric using a fine mist method, and treated at 60℃ for 40 min. The epoxy groups on the fiber surface underwent a ring-opening addition reaction with the amino groups in the DMAEMA molecules, grafting polymerizable methacrylate carbon-carbon double bond active sites onto the other side of the epoxidized cotton fabric. This process was used to further prepare PEG-BA temperature-responsive functional materials. First, polyethylene glycol (PEG, molecular weight approximately 4000) was vacuum dried at 70°C for 10 h, then dissolved in 60 mL of dichloromethane, and 10 g of molecular sieve was added for dehydration. Ethyl methacrylate-2-isocyanate (2-IEM) and DBTDL were added to the above system, with a PEG to 2-IEM mass ratio of 18:1 and DBTDL added at 0.15 wt%. The mixture was stirred at 30°C for 4 days to allow the PEG terminal hydroxyl groups to fully react with the isocyanate groups, obtaining a PEG-based dimethacrylate prepolymer. After the reaction, the resulting product was added to a large amount of n-hexane for precipitation. The precipitate was collected by filtration and vacuum dried at 40°C for 8 h to obtain PEGDM oligomers. Subsequently, the PEGDM oligomer was melted at 70°C and mixed uniformly with butyl acrylate (BA, 12 wt%) and azobisisobutyronitrile (AIBN, 0.3 wt%). This mixture was then dissolved in 10 mL of DMF to prepare a mixed solution, which was deposited onto the other side of the cotton fabric with the introduced methacrylic acid active groups using a fine mist method. The fabric was then heated at 80°C for 24 h to undergo free radical polymerization, allowing it to form a stable bond with the substrate through double bond polymerization, thus forming a PEG-BA temperature-responsive surface. Finally, the prepared bifunctional cotton fabric was washed with dichloromethane, DMF, and distilled water to remove unreacted small molecules, and dried at 80°C for 2 h to obtain a smart cotton fabric with a dual-functional structure of a hydrophilic antibacterial layer and a temperature-responsive hydrophobic layer.

[0041] Performance Testing: After tannic acid treatment, the hydrophilicity of the fabric surface was significantly enhanced, exhibiting excellent hydrophilic properties. The water contact angle on the other side of the surface after PEG-BA functionalization reached over 130°, exhibiting obvious hydrophobic characteristics, proving that the fabric forms a distinct Janus wetting structure. Antibacterial performance results showed that the tannic acid-functionalized surface exhibited excellent antibacterial effects against both *Escherichia coli* and *Staphylococcus aureus*, with an inhibition rate exceeding 99.9%. After 50 standard washes, the fabric still maintained an antibacterial rate of over 95%, indicating that the functional layer has good durability and stability. Water vapor transmission performance testing results showed that the water vapor transmission rate of the cotton fabric at a low temperature of 0℃ was 4.25 g / m³. 2 / d, when the temperature rises to 40℃, the moisture permeability increases, reaching 6.49. .

[0042] Comparative Example 1

[0043] First, the cotton fabric was ultrasonically cleaned with anhydrous ethanol and deionized water for 30 min to remove oil and impurities from the fabric surface. Then, the clean cotton fabric was immersed in an aqueous activating solution containing epichlorohydrin (5 wt%) and sodium hydroxide (3 wt%). The epoxidation heat treatment temperature was 90℃ for 8 min, resulting in the etherification of hydroxyl groups on the cellulose surface and the introduction of epoxy active groups, thus obtaining epoxidized cotton fabric. Next, a 1.2 wt% tannic acid aqueous solution was prepared and deposited onto one side of the epoxidized cotton fabric using a fine mist method. The curing temperature was 170℃ for 4 min. Then, a 7 wt% aminoethyl methacrylate (DMAEMA) aqueous solution was prepared and deposited onto the other side of the epoxidized cotton fabric using a fine mist method, and treated at 60℃ for 40 min. The epoxy groups on the fiber surface underwent a ring-opening addition reaction with the amino groups in the DMAEMA molecules, grafting polymerizable methacrylate carbon-carbon double bond active sites onto the other side of the epoxidized cotton fabric. This process was used to further prepare PEG-BA temperature-responsive functional materials. First, polyethylene glycol (PEG, molecular weight approximately 4000) was vacuum dried at 70°C for 10 h, then dissolved in 60 mL of dichloromethane, and 10 g of molecular sieve was added for dehydration. Ethyl methacrylate-2-isocyanate (2-IEM) and DBTDL were added to the above system, with a PEG to 2-IEM mass ratio of 18:1 and DBTDL added at 0.15 wt%. The mixture was stirred at 30°C for 4 days to allow the PEG terminal hydroxyl groups to fully react with the isocyanate groups, obtaining a PEG-based dimethacrylate prepolymer. After the reaction, the resulting product was added to a large amount of n-hexane for precipitation. The precipitate was collected by filtration and vacuum dried at 40°C for 8 h to obtain PEGDM oligomers. Subsequently, the PEGDM oligomer was melted at 70°C and mixed uniformly with butyl acrylate (BA, 12 wt%) and azobisisobutyronitrile (AIBN, 0.3 wt%). This mixture was then dissolved in 10 mL of DMF to prepare a mixed solution, which was deposited onto the other side of the cotton fabric with the introduced methacrylic acid active groups using a fine mist method. The fabric was then heated at 80°C for 14 h to undergo free radical polymerization, allowing it to form a stable bond with the substrate through double bond polymerization, thus forming a PEG-BA temperature-responsive surface. Finally, the prepared bifunctional cotton fabric was washed with dichloromethane, DMF, and distilled water to remove unreacted small molecules, and dried at 80°C for 2 h to obtain a smart cotton fabric with a dual-functional structure of a hydrophilic antibacterial layer and a temperature-responsive hydrophobic layer.

[0044] Performance Testing: After tannic acid treatment, the hydrophilicity of the fabric surface was slightly enhanced, exhibiting hydrophilic properties. The water contact angle on the other side of the surface after PEG-BA functionalization reached over 115°, exhibiting hydrophobic characteristics, proving that the fabric forms a Janus wetting structure. Antibacterial performance results showed that the tannic acid-functionalized surface had a certain antibacterial effect against both *Escherichia coli* and *Staphylococcus aureus*, with an inhibition rate of 90%. After 50 standard washes, the fabric still maintained an antibacterial rate of over 85%. Water vapor transmission performance testing results showed that the water vapor transmission rate of the cotton fabric at a low temperature of 0℃ was 4.31 g / m³. 2 / d, when the temperature rises to 40℃, the moisture permeability increases, reaching 4.72. .

[0045] Comparative Example 2

[0046] First, the cotton fabric was ultrasonically cleaned with anhydrous ethanol and deionized water for 30 min to remove oil and impurities from the fabric surface. A 1.5 wt% tannic acid aqueous solution was prepared and deposited onto one side of the clean cotton fabric using a fine mist method, with a curing temperature of 170℃ and a treatment time of 5 min. Next, an 8 wt% aminoethyl methacrylate (DMAEMA) aqueous solution was prepared and deposited onto the other side of the clean cotton fabric using a fine mist method, treated at 60℃ for 40 min. Further preparation of the PEG-BA temperature-responsive functional material was then carried out. First, polyethylene glycol (PEG, molecular weight approximately 4000) was vacuum-dried at 70℃ for 10 h, then dissolved in 60 mL of dichloromethane, and 10 g of molecular sieve was added for dehydration. Ethyl 2-isocyanate methacrylate (2-IEM) and DBTDL were added to the above system, with a PEG to 2-IEM mass ratio of 18:1 and a DBTDL addition of 0.15 wt%. The mixture was stirred at 30 °C for 4 days to allow the PEG terminal hydroxyl groups to fully react with the isocyanate groups, obtaining a PEG-based dimethacrylate prepolymer. After the reaction, the product was added to a large amount of n-hexane for precipitation. The precipitate was collected by filtration and vacuum dried at 40 °C for 8 h to obtain PEGDM oligomers. Subsequently, the PEGDM oligomers were melted at 70 °C and mixed evenly with butyl acrylate (BA, 10 wt%) and azobisisobutyronitrile (AIBN, 0.3 wt%). The mixture was then dissolved in 10 mL of DMF to prepare a mixed solution, which was deposited on the other side of a cotton fabric that had been incorporating aminoethyl methacrylate using a fine mist method. The fabric was then heated at 80 °C for 14 h to form a PEG-BA temperature-responsive surface. Finally, the prepared cotton fabric was washed with dichloromethane, DMF and distilled water to remove unreacted small molecules, and dried at 80°C for 2 h to obtain a smart cotton fabric with a dual-functional structure of hydrophilic antibacterial layer / temperature-responsive hydrophobic layer.

[0047] Performance Testing: Antibacterial performance results showed that the tannic acid-functionalized surface exhibited antibacterial effects against both *Escherichia coli* and *Staphylococcus aureus*, with an inhibition rate exceeding 99.9%. After 50 standard washes, the fabric's antibacterial rate was only 30%, indicating that the tannic acid was only physically adsorbed, and the antibacterial performance failed after 50 washes. The other surface, after PEG-BA functionalization, achieved a water contact angle exceeding 131°, demonstrating significant hydrophobic characteristics, proving that the fabric possesses a Janus wetting structure. Water vapor transmission performance testing results showed that the cotton fabric had a water vapor transmission rate of 4.56 g / m² at 0℃. 2 / d, when the temperature rises to 40℃, the moisture permeability increases, reaching 5.73. .

[0048] Comparative Example 3

[0049] First, the cotton fabric was ultrasonically cleaned with anhydrous ethanol and deionized water for 30 min to remove oil and impurities from the fabric surface. Then, the clean cotton fabric was immersed in an aqueous activating solution containing epichlorohydrin (10 wt%) and sodium hydroxide (3 wt%). The epoxidation heat treatment temperature was 90℃ for 8 min, resulting in the etherification of hydroxyl groups on the cellulose surface and the introduction of epoxy active groups, thus obtaining epoxidized cotton fabric. Next, a 1.2 wt% tannic acid aqueous solution was prepared and deposited onto one side of the epoxidized cotton fabric using a fine mist method. The curing temperature was 170℃ for 4 min. Then, a 7 wt% aminoethyl methacrylate (DMAEMA) aqueous solution was prepared and deposited onto both sides of the epoxidized cotton fabric using a fine mist method, and treated at 60℃ for 40 min. The epoxy groups on the fiber surface underwent a ring-opening addition reaction with the amino groups in the DMAEMA molecules, grafting polymerizable methacrylate carbon-carbon double bond active sites onto both sides of the epoxidized cotton fabric. This process was used to further prepare PEG-BA temperature-responsive functional materials. First, polyethylene glycol (PEG, molecular weight approximately 4000) was vacuum dried at 70°C for 10 h, then dissolved in 60 mL of dichloromethane, and 10 g of molecular sieve was added for dehydration. Ethyl methacrylate-2-isocyanate (2-IEM) and DBTDL were added to the above system, with a PEG to 2-IEM mass ratio of 18:1 and DBTDL added at 0.15 wt%. The mixture was stirred at 30°C for 4 days to allow the PEG terminal hydroxyl groups to fully react with the isocyanate groups, obtaining a PEG-based dimethacrylate prepolymer. After the reaction, the resulting product was added to a large amount of n-hexane for precipitation. The precipitate was collected by filtration and vacuum dried at 40°C for 8 h to obtain PEGDM oligomers. Subsequently, the PEGDM oligomer was melted at 70°C and mixed uniformly with butyl acrylate (BA, 12 wt%) and azobisisobutyronitrile (AIBN, 0.3 wt%). This mixture was then dissolved in 10 mL of DMF to prepare a mixed solution, which was deposited onto both sides of the cotton fabric with the introduced methacrylic acid active groups using a fine mist method. The fabric was then heated at 80°C for 14 h to undergo free radical polymerization, allowing it to form a stable bond with the substrate through double bond polymerization, thus creating a PEG-BA temperature-responsive surface. Finally, the prepared bifunctional cotton fabric was washed with dichloromethane, DMF, and distilled water to remove unreacted small molecules, and dried at 80°C for 2 h to obtain a smart cotton fabric with an antibacterial structure.

[0050] Performance testing: The water contact angle on both sides of the PEG-BA-functionalized surface reached over 130°. Antibacterial performance results showed that the tannic acid-functionalized surface exhibited excellent antibacterial effects against both *Escherichia coli* and *Staphylococcus aureus*, with an inhibition rate exceeding 99.9%. After 50 standard washes, the fabric still maintained an antibacterial rate of over 95%, indicating that the functional layer has good durability and stability. Water vapor transmission performance testing results showed that the water vapor transmission rate of the cotton fabric at a low temperature of 0℃ was 4.33 g / m². 2 / d, when the temperature rises to 40℃, the moisture permeability increases, reaching 4.78. The fabric is coated with PEG-BA temperature-sensitive coating on both sides, with no functional difference between the two sides, and does not have a unidirectional moisture-wicking effect.

[0051] Comparative Example 4

[0052] First, the cotton fabric was ultrasonically cleaned with anhydrous ethanol and deionized water for 30 min to remove oil and impurities from the fabric surface. Then, the clean cotton fabric was immersed in an aqueous activating solution containing epichlorohydrin (10 wt%) and sodium hydroxide (4 wt%). The epoxidation heat treatment temperature was 100℃ for 6 min, resulting in the etherification of hydroxyl groups on the cellulose surface and the introduction of epoxy active groups, thus obtaining epoxidized cotton fabric. Next, a 7 wt% aqueous solution of aminoethyl methacrylate (DMAEMA) was prepared and deposited onto one side of the epoxidized cotton fabric using a fine mist method, followed by treatment at 60℃ for 40 min. The epoxy groups on the fiber surface underwent a ring-opening addition reaction with the amino groups in the DMAEMA molecules, grafting polymerizable methacrylate carbon-carbon double bond active sites onto the other side of the epoxidized cotton fabric. This process was then used to prepare PEG-BA temperature-responsive functional materials. First, polyethylene glycol (PEG, molecular weight approximately 4000) was vacuum dried at 70°C for 10 h, then dissolved in 60 mL of dichloromethane, and 10 g of molecular sieve was added for dehydration. Ethyl methacrylate-2-isocyanate (2-IEM) and DBTDL were added to the above system, with a PEG to 2-IEM mass ratio of 18:1 and DBTDL added at 0.15 wt%. The mixture was stirred at 30°C for 4 days to allow the PEG terminal hydroxyl groups to fully react with the isocyanate groups, obtaining a PEG-based dimethacrylate prepolymer. After the reaction, the resulting product was added to a large amount of n-hexane for precipitation. The precipitate was collected by filtration and vacuum dried at 40°C for 8 h to obtain PEGDM oligomers. Subsequently, the PEGDM oligomer was melted at 70°C and mixed uniformly with butyl acrylate (BA, 20 wt%) and azobisisobutyronitrile (AIBN, 0.4 wt%). This mixture was then dissolved in 10 mL of DMF to prepare a mixed solution, which was deposited onto one side of the cotton fabric with the introduced methacrylic acid active groups using a fine mist method. The fabric was then heated at 85°C for 16 h to undergo free radical polymerization, allowing it to form a stable bond with the substrate through double bond polymerization, thus forming a PEG-BA temperature-responsive surface. Finally, the prepared bifunctional cotton fabric was washed with dichloromethane, DMF, and distilled water to remove unreacted small molecules, and dried at 80°C for 2 h to obtain a smart cotton fabric with a dual-functional structure of a hydrophilic antibacterial layer and a temperature-responsive hydrophobic layer.

[0053] Performance testing: The water contact angle on one side of the surface after PEG-BA functionalization reached over 133°, exhibiting hydrophobic characteristics. Antibacterial performance results showed that the prepared cotton fabric had no inhibitory effect on Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). Water vapor transmission performance testing results showed that the water vapor transmission rate of the cotton fabric at a low temperature of 0℃ was 4.39 g / m². 2 / d, when the temperature rises to 40℃, the moisture permeability increases, reaching 4.94. .

[0054] Comparative Example 5

[0055] First, the cotton fabric was ultrasonically cleaned with anhydrous ethanol and deionized water for 30 min to remove oil and impurities from the fabric surface. Then, the clean cotton fabric was immersed in an aqueous activating solution containing epichlorohydrin (10 wt%) and sodium hydroxide (4 wt%). The epoxidation heat treatment temperature was 80℃ for 5 min, resulting in the etherification of hydroxyl groups on the cellulose surface and the introduction of epoxy active groups, thus obtaining epoxidized cotton fabric. Next, a 1.2 wt% tannic acid aqueous solution was prepared and deposited onto one side of the epoxidized cotton fabric using a fine mist method. The curing temperature was 180℃ for 5 min. Then, a 7 wt% aminoethyl methacrylate (DMAEMA) aqueous solution was prepared and deposited onto the other side of the epoxidized cotton fabric using a fine mist method, and treated at 60℃ for 40 min. The epoxy groups on the fiber surface underwent a ring-opening addition reaction with the amino groups in the DMAEMA molecules, grafting polymerizable methacrylate carbon-carbon double bond active sites onto the other side of the epoxidized cotton fabric. This process was used to further prepare PEG-BA temperature-responsive functional materials. First, polyethylene glycol (PEG, molecular weight approximately 4000) was vacuum dried at 70°C for 10 h, then dissolved in 60 mL of dichloromethane, and 10 g of molecular sieve was added for dehydration. Ethyl methacrylate-2-isocyanate (2-IEM) and DBTDL were added to the above system, with a PEG to 2-IEM mass ratio of 18:1 and DBTDL added at 0.15 wt%. The mixture was stirred at 30°C for 4 days to allow the PEG terminal hydroxyl groups to fully react with the isocyanate groups, obtaining a PEG-based dimethacrylate prepolymer. After the reaction, the resulting product was added to a large amount of n-hexane for precipitation. The precipitate was collected by filtration and vacuum dried at 40°C for 8 h to obtain PEGDM oligomers. Subsequently, the PEGDM oligomer was melted at 70°C and mixed uniformly with butyl acrylate (BA, 12 wt%) and azobisisobutyronitrile (AIBN, 0.3 wt%). This mixture was then dissolved in 10 mL of DMF to prepare a mixed solution, which was deposited onto the other side of the cotton fabric with the introduced methacrylic acid active groups using a fine mist method. The fabric was then heated at 80°C for 24 h to undergo free radical polymerization, allowing it to form a stable bond with the substrate through double bond polymerization, thus forming a PEG-BA temperature-responsive surface. Finally, the prepared bifunctional cotton fabric was washed with dichloromethane, DMF, and distilled water to remove unreacted small molecules, and dried at 80°C for 2 h to obtain a smart cotton fabric with a dual-functional structure of a hydrophilic antibacterial layer and a temperature-responsive hydrophobic layer.

[0056] Performance Testing: After tannic acid treatment, the hydrophilicity of the fabric surface was enhanced; the water contact angle on the other side of the surface after PEG-BA functionalization reached over 128°, exhibiting hydrophobic characteristics, proving that the fabric formed a Janus wetting structure. Antibacterial performance results showed that the tannic acid-functionalized surface exhibited excellent antibacterial effects against Escherichia coli and Staphylococcus aureus, with an inhibition rate exceeding 98%. After 50 standard washes, the fabric still maintained an antibacterial rate of over 95%; water vapor transmission performance test results showed that the water vapor transmission rate of the cotton fabric at a low temperature of 0℃ was 4.27 g / m³. 2 / d, when the temperature rises to 40℃, the moisture permeability increases, reaching 5.64. .

[0057] Comparative Example 6

[0058] First, the cotton fabric was pretreated with anhydrous ethanol and deionized water to remove oil and impurities from the fabric surface. The clean cotton fabric was then immersed in an aqueous activation solution containing epichlorohydrin and sodium hydroxide. The hydroxyl groups on the cellulose surface underwent an etherification reaction, introducing epoxy active groups to obtain an epoxy-coated cotton fabric. The solvent was deionized water, with epichlorohydrin at 10 wt% and sodium hydroxide at 4 wt%. The epoxidation heat treatment temperature was 100℃ for 6 min. Subsequently, tannic acid at 1.2 wt% was prepared and deposited onto one side of the epoxy-coated cotton fabric using a fine mist method. The curing temperature was 160℃ for 3 min. Next, an aqueous solution of aminoethyl methacrylate (DMAEMA) at 7 wt% was prepared and deposited onto the other side of the epoxy-coated cotton fabric using a fine mist method. After pre-drying at 60℃ for 30 min, the epoxy groups on the fiber surface underwent a ring-opening addition reaction with the amino groups in the DMAEMA molecules, grafting polymerizable methacrylate carbon-carbon double bond active sites onto the other side of the cotton fiber surface. Further preparation of PEG-BA temperature-responsive functional materials was carried out. First, polyethylene glycol (PEG, molecular weight approximately 4000) was vacuum dried at 70 °C for 10 h, then dissolved in 60 mL of dichloromethane, and 10 g of molecular sieve was added for dehydration. Ethyl methacrylate-2-isocyanate and DBTDL were added to the above system, with a PEG to 2-IEM mass ratio of 18:1 and DBTDL added at 0.2 wt%. The mixture was stirred at 30 °C for 4 days to allow the PEG terminal hydroxyl groups to fully react with the isocyanate groups, obtaining a PEG-based dimethacrylate prepolymer. After the reaction, the obtained product was added to a large amount of n-hexane for precipitation. The precipitate was collected by filtration and vacuum dried at 40 °C for 8 h to obtain PEGDM oligomers. Subsequently, the PEGDM oligomer was melted at 70°C and mixed uniformly with butyl acrylate (BA, 12 wt%) and azobisisobutyronitrile (AIBN, 0.3 wt%). This mixture was then dissolved in 10 mL of DMF to prepare a mixed solution, which was atomized and deposited onto the other side of the cotton fabric with the introduced methacrylic acid active groups. The fabric was then heated at 80°C for 24 h to undergo free radical polymerization, allowing it to form a stable bond with the substrate through double bond polymerization, thus forming a PEG-BA temperature-responsive surface. Finally, the prepared bifunctional cotton fabric was washed with dichloromethane and distilled water to remove unreacted small molecules, and dried at 80°C for 2 h to obtain a smart cotton fabric with a dual-functional structure of a hydrophilic antibacterial layer and a temperature-responsive hydrophobic layer.

[0059] Performance Testing: After tannic acid treatment, the hydrophilicity of the fabric surface was enhanced; the water contact angle on the other side of the surface after PEG-BA functionalization reached over 132°, exhibiting hydrophobic characteristics, proving that the fabric formed a Janus wetting structure. Antibacterial performance results showed that the tannic acid-functionalized surface exhibited antibacterial effects against both *Escherichia coli* and *Staphylococcus aureus*, with an inhibition rate exceeding 85%. After 50 standard washes, the fabric still maintained an antibacterial rate of over 70%; water vapor transmission performance test results showed that the water vapor transmission rate of the cotton fabric at a low temperature of 0℃ was 4.35 g / (m²). 2 ·d) When the temperature rises to 40℃, the moisture permeability increases, reaching 5.84. .

[0060] Comparative Example 7

[0061] First, the cotton fabric was pretreated with anhydrous ethanol and deionized water to remove oil and impurities from the fabric surface. The clean cotton fabric was then immersed in an aqueous activation solution containing epichlorohydrin and sodium hydroxide. The hydroxyl groups on the cellulose surface underwent an etherification reaction, introducing epoxy active groups to obtain an epoxy-coated cotton fabric. The solvent was deionized water, with epichlorohydrin at 10 wt% and sodium hydroxide at 4 wt%. The epoxidation heat treatment temperature was 100℃ for 6 min. Subsequently, 1.2 wt% tannic acid was prepared and deposited onto one side of the epoxy-coated cotton fabric using a fine mist method. The curing temperature was 180℃ for 5 min. Next, a 5 wt% aqueous solution of aminoethyl methacrylate (DMAEMA) was prepared and deposited onto the other side of the epoxy-coated cotton fabric using a fine mist method. After pre-drying at 60℃ for 30 min, the epoxy groups on the fiber surface underwent a ring-opening addition reaction with the amino groups in the DMAEMA molecules, grafting polymerizable methacrylate carbon-carbon double bond active sites onto the other side of the cotton fiber surface. Further preparation of PEG-BA temperature-responsive functional materials was carried out. First, polyethylene glycol (PEG, molecular weight approximately 4000) was vacuum dried at 70 °C for 10 h, then dissolved in 60 mL of dichloromethane, and 10 g of molecular sieve was added for dehydration. Ethyl methacrylate-2-isocyanate and DBTDL were added to the above system, with a PEG to 2-IEM mass ratio of 18:1 and DBTDL added at 0.2 wt%. The mixture was stirred at 30 °C for 4 days to allow the PEG terminal hydroxyl groups to fully react with the isocyanate groups, obtaining a PEG-based dimethacrylate prepolymer. After the reaction, the obtained product was added to a large amount of n-hexane for precipitation. The precipitate was collected by filtration and vacuum dried at 40 °C for 8 h to obtain PEGDM oligomers. Subsequently, the PEGDM oligomer was melted at 70°C and mixed uniformly with butyl acrylate (BA, 12 wt%) and azobisisobutyronitrile (AIBN, 0.3 wt%). This mixture was then dissolved in 10 mL of DMF to prepare a mixed solution, which was atomized and deposited onto the other side of the cotton fabric with the introduced methacrylic acid active groups. The fabric was then heated at 80°C for 24 h to undergo free radical polymerization, allowing it to form a stable bond with the substrate through double bond polymerization, thus forming a PEG-BA temperature-responsive surface. Finally, the prepared bifunctional cotton fabric was washed with dichloromethane and distilled water to remove unreacted small molecules, and dried at 80°C for 2 h to obtain a smart cotton fabric with a dual-functional structure of a hydrophilic antibacterial layer and a temperature-responsive hydrophobic layer.

[0062] Performance Testing: After tannic acid treatment, the hydrophilicity of the fabric surface was enhanced; the water contact angle on the other side of the surface after PEG-BA functionalization reached over 128°, exhibiting hydrophobic characteristics, proving that the fabric formed a Janus wetting structure. Antibacterial performance results showed that the tannic acid-functionalized surface exhibited antibacterial effects against both *Escherichia coli* and *Staphylococcus aureus*, with an inhibition rate exceeding 99.9%. After 50 standard washes, the fabric still maintained an antibacterial rate of over 95%; water vapor transmission performance test results showed that the water vapor transmission rate of the cotton fabric at a low temperature of 0℃ was 4.29%. When the temperature rises to 40℃, the moisture permeability increases, reaching 5.61. .

[0063] Comparative Example 8

[0064] First, the cotton fabric was pretreated with anhydrous ethanol and deionized water to remove oil and impurities from the fabric surface. The clean cotton fabric was then immersed in an aqueous activation solution containing epichlorohydrin and sodium hydroxide. The hydroxyl groups on the cellulose surface underwent an etherification reaction, introducing epoxy active groups to obtain an epoxy-coated cotton fabric. The solvent was deionized water, with epichlorohydrin at 10 wt% and sodium hydroxide at 4 wt%. The epoxidation heat treatment temperature was 100℃ for 6 min. Subsequently, tannic acid at 1.2 wt% was prepared and deposited onto one side of the epoxy-coated cotton fabric using a fine mist method. The curing temperature was 180℃ for 5 min. Next, an aqueous solution of aminoethyl methacrylate (DMAEMA) at 7 wt% was prepared and deposited onto the other side of the epoxy-coated cotton fabric using a fine mist method. After pre-drying at 60℃ for 30 min, the epoxy groups on the fiber surface underwent a ring-opening addition reaction with the amino groups in the DMAEMA molecules, grafting polymerizable methacrylate carbon-carbon double bond active sites onto the other side of the cotton fiber surface. Further preparation of PEG-BA temperature-responsive functional materials was carried out. First, polyethylene glycol (PEG, molecular weight approximately 4000) was vacuum dried at 70 °C for 10 h, then dissolved in 60 mL of dichloromethane, and 10 g of molecular sieve was added for dehydration. Ethyl methacrylate-2-isocyanate and DBTDL were added to the above system, with a PEG to 2-IEM mass ratio of 18:1 and DBTDL added at 0.2 wt%. The mixture was stirred at 30 °C for 4 days to allow the PEG terminal hydroxyl groups to fully react with the isocyanate groups, obtaining a PEG-based dimethacrylate prepolymer. After the reaction, the obtained product was added to a large amount of n-hexane for precipitation. The precipitate was collected by filtration and vacuum dried at 40 °C for 8 h to obtain PEGDM oligomers. Subsequently, the PEGDM oligomer was melted at 70°C and mixed uniformly with butyl acrylate (BA, 33 wt%) and azobisisobutyronitrile (AIBN, 0.2 wt%). This mixture was then dissolved in 10 mL of DMF to prepare a mixed solution, which was atomized and deposited onto the other side of the cotton fabric with the introduced methacrylic acid active groups. The fabric was then heated at 85°C for 16 h to undergo free radical polymerization, allowing it to form a stable bond with the substrate through double bond polymerization, thus forming a PEG-BA temperature-responsive surface. Finally, the prepared bifunctional cotton fabric was washed with dichloromethane and distilled water to remove unreacted small molecules, and dried at 80°C for 2 h to obtain a smart cotton fabric with a dual-functional structure of a hydrophilic antibacterial layer and a temperature-responsive hydrophobic layer.

[0065] Performance Testing: After tannic acid treatment, the hydrophilicity of the fabric surface was enhanced; the water contact angle on the other side of the surface after PEG-BA functionalization reached over 130°, exhibiting hydrophobic characteristics, proving that the fabric formed a Janus wetting structure. Antibacterial performance results showed that the tannic acid-functionalized surface exhibited antibacterial effects against both *Escherichia coli* and *Staphylococcus aureus*, with an inhibition rate exceeding 99.9%. After 50 standard washes, the fabric still maintained an antibacterial rate of over 95%; water vapor transmission performance test results showed that the water vapor transmission rate of the cotton fabric at a low temperature of 0℃ was 4.64%. When the temperature rises to 40℃, the moisture permeability increases, reaching 4.86g / (m²·d).

[0066] Comparative Example 9

[0067] First, the cotton fabric was pretreated with anhydrous ethanol and deionized water to remove oil and impurities from the fabric surface. The clean cotton fabric was then immersed in an aqueous activation solution containing epichlorohydrin and sodium hydroxide. The hydroxyl groups on the cellulose surface underwent an etherification reaction, introducing epoxy active groups to obtain an epoxy-coated cotton fabric. The solvent was deionized water, with epichlorohydrin at 10 wt% and sodium hydroxide at 4 wt%. The epoxidation heat treatment temperature was 100℃ for 6 min. Subsequently, tannic acid at 1.2 wt% was prepared and deposited onto one side of the epoxy-coated cotton fabric using a fine mist method. The curing temperature was 180℃ for 5 min. Next, an aqueous solution of aminoethyl methacrylate (DMAEMA) at 7 wt% was prepared and deposited onto the other side of the epoxy-coated cotton fabric using a fine mist method. After pre-drying at 60℃ for 30 min, the epoxy groups on the fiber surface underwent a ring-opening addition reaction with the amino groups in the DMAEMA molecules, grafting polymerizable methacrylate carbon-carbon double bond active sites onto the other side of the cotton fiber surface. Further preparation of PEG-BA temperature-responsive functional materials was carried out. First, polyethylene glycol (PEG, molecular weight approximately 4000) was vacuum dried at 70 °C for 10 h, then dissolved in 60 mL of dichloromethane, and 10 g of molecular sieve was added for dehydration. Ethyl methacrylate-2-isocyanate and DBTDL were added to the above system, with a PEG to 2-IEM mass ratio of 18:1 and DBTDL added at 0.2 wt%. The mixture was stirred at 30 °C for 4 days to allow the PEG terminal hydroxyl groups to fully react with the isocyanate groups, obtaining a PEG-based dimethacrylate prepolymer. After the reaction, the obtained product was added to a large amount of n-hexane for precipitation. The precipitate was collected by filtration and vacuum dried at 40 °C for 8 h to obtain PEGDM oligomers. Subsequently, the PEGDM oligomer was melted at 70°C and mixed uniformly with butyl acrylate (BA, 12 wt%) and azobisisobutyronitrile (AIBN, 0.3 wt%). This mixture was then dissolved in 10 mL of DMF to prepare a mixed solution, which was atomized and deposited onto the other side of the cotton fabric with the introduced methacrylic acid active groups. The fabric was then heated at 70°C for 12 h to undergo free radical polymerization, allowing it to form a stable bond with the substrate through double bond polymerization, thus forming a PEG-BA temperature-responsive surface. Finally, the prepared bifunctional cotton fabric was washed with dichloromethane and distilled water to remove unreacted small molecules, and dried at 80°C for 2 h to obtain a smart cotton fabric with a dual-functional structure of a hydrophilic antibacterial layer and a temperature-responsive hydrophobic layer.

[0068] Performance Testing: After tannic acid treatment, the hydrophilicity of the fabric surface was enhanced; the water contact angle on the other side of the surface after PEG-BA functionalization reached over 130°, exhibiting hydrophobic characteristics, proving that the fabric formed a Janus wetting structure. Antibacterial performance results showed that the tannic acid-functionalized surface exhibited antibacterial effects against both *Escherichia coli* and *Staphylococcus aureus*, with an inhibition rate exceeding 99.9%. After 50 standard washes, the fabric still maintained an antibacterial rate of over 95%; water vapor transmission performance test results showed that the water vapor transmission rate of the cotton fabric at a low temperature of 0℃ was 4.79%. When the temperature rises to 40℃, the moisture permeability increases, reaching 5.03. .

[0069] Comparison of experimental parameters between the examples and comparative examples:

[0070]

[0071] Comparison of experimental results between the examples and the comparative examples:

[0072]

[0073] As can be seen from the above embodiments and comparative examples:

[0074] Examples 1-4 represent the optimal process combination within the parameter range defined in the claims of this invention. All four groups of samples fully realize the three core functions of Janus: double-sided heterogeneous structure, long-lasting covalent antibacterial effect, and positive reversible temperature-sensitive moisture permeability. All performance indicators fully meet the standards and are superior to all comparative examples.

[0075] (1) Wetting difference (Janus structure): The water contact angle on the hydrophobic side is ≥130°, and the tannic acid layer on the hydrophilic side can spread water droplets quickly, with significant differences in wettability between the front and back sides;

[0076] (2) Antibacterial and washable durability: The antibacterial rate against Escherichia coli and Staphylococcus aureus is 99.9%. After 50 standard washes, the antibacterial rate is maintained at more than 96% with no significant decrease.

[0077] (3) Positive temperature response moisture permeability: Water vapor transmission rate at low temperature (0℃) is 3.71-4.25%. At a high temperature of 40℃, the moisture permeability increases to 6.32-6.89. , the difference between high and low temperature moisture permeability ≥ 2.0 It has a wide temperature-sensitive control range and a large response amplitude, and outstanding low-temperature heat retention and high-temperature moisture conduction effects.

[0078] Univariate proportional grouping analysis:

[0079] (1) The epoxy activation system (epoxychloropropane, heat treatment) is the basis for long-lasting antibacterial effect (Comparative Example 1, Comparative Example 5)

[0080] Comparative Example 1: epichlorohydrin was only 5 wt%, with insufficient epoxidation sites and a decrease in tannic acid grafting; the antibacterial rate was only 90%, which dropped to 85% after 50 water washes; the hydrophobic contact angle was only 115°; the Janus interface was unclear; and the anchoring strength of the temperature-sensitive layer decreased.

[0081] Comparative Example 5: The epoxidation heat treatment was only 80℃ / 5 min, resulting in incomplete reaction, reduced antibacterial rate to 98%, and slight decrease in water washability.

[0082] Conclusion: Heat treatment with epichlorohydrin at 8-15 wt% and 80-110℃ for 5-12 min is a necessary condition to ensure sufficient epoxy active sites and achieve covalent anchoring of tannic acid and temperature-sensitive polymer. Parameters below this range will directly lead to a significant decrease in antibacterial durability and hydrophobic properties.

[0083] (2) The epoxy activation step cannot be omitted; it is the key to the covalent grafting of tannic acid (Comparative Example 2).

[0084] Comparative Example 2 was not epoxy activated. Tannins adhered to the fiber surface only through physical adsorption. Although the antibacterial rate reached 99.9%, it dropped sharply to 30% after 50 washes, and the antibacterial function was basically ineffective. It could not resist washing by relying solely on intermolecular forces and could not meet the requirements for long-term antibacterial use.

[0085] Conclusion: The alkaline epoxidation activation of epichlorohydrin is the core innovative step for achieving covalent grafting of tannic acid and improving water washability. Omitting this step will result in the loss of the core advantage of the present invention: durable antibacterial properties.

[0086] (3) Single-sided directional spraying is the key to forming the two-sided differentiation of Janus (Comparative Example 3).

[0087] Comparative Example 3 fabric was coated with DMAEMA and PEG-BA thermosensitive liquids on both sides, with hydrophobic thermosensitive layers on both sides, showing no difference in wetting between the two sides; the difference in moisture permeability at high and low temperatures was only 0.45. It lacks the ability to conduct moisture in one direction and regulate hot and cold zones, thus losing the core value of the Janus structure.

[0088] Conclusion: The single-sided fine mist deposition process is a necessary method for constructing an asymmetric structure with one side being hydrophilic and antibacterial, and the other side being thermosensitive and hydrophobic. Double-sided spraying eliminates the functional differences between the two sides and cannot achieve zonal temperature and humidity control of the human body.

[0089] (4) The hydrophilic antibacterial layer of tannic acid is an essential functional layer (Comparative Example 4)

[0090] Comparative Example 4, which was not sprayed with tannic acid functional liquid, had no hydrophilic antibacterial interface, and its antibacterial rate against both pathogens was 0, completely losing its antibacterial properties; at the same time, it lacked hydrophilic capillary channels, so sweat could not be quickly conducted to the hydrophobic side, and its one-way moisture-wicking function failed.

[0091] Conclusion: Unilateral tannic acid fine mist grafting is a necessary step to simultaneously achieve hydrophilicity and moisture wicking in fabrics and plant-derived antibacterial properties. Without this layer, the material has no medical or intimate apparel application value.

[0092] (5) Basis for limiting the range of tannic acid curing process parameters (Comparative Example 6)

[0093] Comparative Example 6: Tannic acid was cured at only 160℃ for 3 min, the phenolic hydroxyl group and epoxy ring-opening reaction was incomplete, and the amount of tannic acid grafted was insufficient; the original antibacterial rate was only 85%, and after 50 water washes, only 70% of the durable antibacterial performance remained.

[0094] Conclusion: Curing with tannic acid at 160-190℃ for 3-8 min can ensure that the phenolic hydroxyl groups fully covalently react with the epoxy groups. Curing temperature / time below this range will significantly reduce the antibacterial durability.

[0095] (6) Validation of the lower limit of DMAEMA addition (Comparative Example 7)

[0096] Comparative Example 7, with a DMAEMA mass fraction of 5 wt%, still achieved 99.9% antibacterial activity and 95% antibacterial rate after 50 washes. A value lower than this would result in insufficient polymerizable double bonds on the fiber surface and a decrease in the anchoring strength of the temperature-sensitive layer.

[0097] (7) Effects of PEGDM to BA ratio and polymerization process on the amplitude of temperature-sensitive response (Comparative Example 8, Comparative Example 9)

[0098] Comparative Example 8 had an excessively high BA ratio (PEGDM:BA=3:1), resulting in an excessive amount of flexible butyl ester segments. This limited the thermosensitive polymer's ability to shrink at low temperatures and expand at high temperatures, leading to a moisture permeability difference of only 0.22 between high and low temperatures. The temperature control effect is weak;

[0099] Comparative Example 9 showed that free radical polymerization at only 70℃ for 12 h resulted in incomplete polymerization, insufficient PEG-BA crosslinking density, poor reversibility of temperature-sensitive segment conformation, and a high-low temperature moisture permeability difference of only 0.24. ;

[0100] Conclusion: To ensure the integrity of the temperature-sensitive polymer crosslinking network, the PEGDM:BA ratio must be controlled at 3:1 to 10:1, and the polymerization temperature at 70 to 90°C for 12 to 36 hours. This allows for dynamic adjustment of the water vapor permeability with large temperature differences. Deviating from the parameter range will directly result in the loss of the intelligent temperature-sensitive heat-locking and moisture-wicking effect.

Claims

1. A method for preparing a low-temperature heat-locking, high-temperature moisture-wicking Janus antibacterial temperature-sensitive cotton fabric using a fine mist method, characterized in that, Includes the following steps: (1) Pretreatment of cotton fabric and epoxy activation treatment: The cotton fabric is ultrasonically cleaned with anhydrous ethanol and deionized water in sequence to remove surface dust and oil. Then, the cleaned and decontaminated cotton fabric is immersed in an aqueous activation solution containing epichlorohydrin and sodium hydroxide. The hydroxyl groups on the surface of cellulose undergo etherification reaction to introduce epoxy active groups, thus obtaining epoxy cotton fabric. (2) Single-sided construction of hydrophilic antibacterial layer: Tannic acid TA functional liquid is deposited on one side of the surface of epoxidized cotton fabric by fine mist method, and heat treatment is performed to open the ring covalent grafting of tannic acid phenolic hydroxyl groups and fiber epoxy groups to form a stable hydrophilic antibacterial functional layer. (3) Introduction of polymerizable carbon-carbon double bonds on one side: The aqueous solution of aminoethyl methacrylate (DMAEMA) is deposited on the other side of the epoxidized cotton fabric using a fine mist method. The epoxy group undergoes ring-opening addition with the amino group, and polymerizable methacrylate double bonds are grafted onto the fiber surface. (4) Constructing a temperature-responsive hydrophobic layer: First, polyethylene glycol dimethacrylate (PEGDM) prepolymer is synthesized; dibutyltin dilaurate (DBTDL) catalyst is added to the synthesis system, and the amount of DBTDL added is 0.15 wt% of the total mass of the reactants. Then, PEGDM, butyl acrylate (BA), and free radical initiator AIBN are mixed to prepare a temperature-sensitive finishing solution, which is deposited on one side of the cotton fabric with active methacrylic acid groups by fine mist method. Free radical polymerization occurs with the polymerizable double bonds on the surface of the cotton fabric to construct a PEG-BA temperature-responsive hydrophobic functional layer. (5) Washing and drying post-treatment: wash away unreacted small molecules and residual additives to obtain a low-temperature heat-locking and high-temperature moisture-wicking Janus antibacterial temperature-sensitive cotton fabric with hydrophilic antibacterial properties on one side and temperature-responsive hydrophobic properties on the other side.

2. The method for preparing a low-temperature heat-locking, high-temperature moisture-wicking Janus antibacterial thermosensitive cotton fabric using a fine mist method according to claim 1, characterized in that: In step (1), the mass fraction of epichlorohydrin is 8~15 wt%, sodium hydroxide is 2~5 wt%, the epoxidation heat treatment temperature is 80~110℃, and the heat treatment time is 5~12 min.

3. The method for preparing a low-temperature heat-locking, high-temperature moisture-wicking Janus antibacterial thermosensitive cotton fabric using a fine mist method according to claim 1, characterized in that: In step (2), the tannic acid functional liquid has a tannic acid mass fraction of 1~1.5 wt%, a curing temperature of 160~190℃, and a processing time of 3~8 min.

4. The method for preparing a low-temperature heat-locking, high-temperature moisture-wicking Janus antibacterial thermosensitive cotton fabric using a fine mist method according to claim 1, characterized in that: The DMAEMA mass fraction in step (3) is 5~8 wt%.

5. The method for preparing a low-temperature heat-locking, high-temperature moisture-wicking Janus antibacterial thermosensitive cotton fabric using a fine mist method according to claim 1, characterized in that: In step (4), the mass ratio of PEGDM to BA in the temperature-sensitive finishing solution is 3:1 to 10:1; the amount of free radical initiator AIBN added is 0.2 to 0.5 wt%; the free radical polymerization temperature is 70 to 90℃, and the time is 12 to 36 h.

6. The method for preparing a low-temperature heat-locking, high-temperature moisture-wicking Janus antibacterial thermosensitive cotton fabric using a fine mist method according to claim 1, characterized in that: The cleaning process in step (5) involves first soaking in DMF to remove organic residues, then washing with deionized water multiple times, and drying at a temperature of 60~90℃.

7. The low-temperature heat-locking, high-temperature moisture-wicking Janus antibacterial thermosensitive cotton fabric prepared by the preparation method according to any one of claims 1-6, characterized in that: The fabric has a bi-directional anisotropic Janus wetting structure, with one side of the fabric being a tannic acid covalently grafted hydrophilic antibacterial layer and the other side being a PEG-BA covalently polymerized temperature-responsive hydrophobic layer.

Citation Information

Patent Citations

  • Impurity compound as well as preparation method and application thereof

    CN117384129A

  • Construction method for downstream flow guarantee supply in high dam and large reservoir in-situ reconstruction

    CN118223456A